MIOCENE SCLERACTINIAN CORALS OF GAVDOS ISLAND, SOUTHERN GREECE: IMPLICATIONS FOR TECTONIC CONTROL AND SEA-LEVEL CHANGES - Drinia, H.; Pomoni-Papaioannou, F.; N., Tsaparas; Antonarakou, A. (Bulletin of the Geological Society of Greece, 2010)
Low-diversity scleractinian patch reefs that have been developed, during Early to Middle Tortonian, in Gavdos island are studied, aiming in a better understanding of the time and space relationships of the reef development and the associated basin fill evolution. Gavdos island consists part of a tectonically active setting constituting the southernmost extension of the Hellenic arc (Eastern Mediterranean). A representative Tortonian section (Bo section), located in the northwest part of the island, which hosts a mass occurrence of hermatypic corals, is studied. Scleractinian samples were collected from the upper 12 m of the section, which is characterized by interchanges of marly limestone and compact marls. The reefs are represented by the coral species Heliastraea oligophylla, Porites maicientensis, Thegioastraea roasendai and Porites collegniana. The microfacies analysis showed that the mediumto-thin-bedded carbonates of the limestone-marl alternations comprise patch reefs (boundstones-framestones, SMF 16, sensu Wilson, 1975, FZ 7-8, sensu Flügel 1982) consisted of screractinian corals. Corals are associated with corallinacean algae. Patch reefs are associated by bioclastic packstones-floatstones, characterized by benthic foraminifera, calcareous algae, spines of echinoids, gastropods and molluscs. Reefs are laterally associated by a bioclastic limestone rich in planktonic forams, associated by detrital material (fragments of quartz, feldspars, quartzites and cherts). The studied reef facies have been dolomitized and cemented in the meteoric realm. In places pseudomorphs after evaporites have been observed, tending to occlude cavities resulted after dissolution. The depositional environment corresponds to a moderate to high-energy inner platform setting, experiencing open-ocean influences. The pattern of coralgal reef development during Miocene, in the tectonically controlled Gavdos island, represents a complex interaction of tectonic activity and global sea-level changes.